FAR1/FHY3 Transcription Factors Positively Regulate the Salt and Temperature Stress Responses in Eucalyptus grandis - Dai, Jiahao; Sun, Jin; Peng, Wenjing; Liao, Wenhai; Zhou, Yuhan; Zhou, Xue-Rong; Qin, Yuan; Cheng, Yan; Cao, Shijiang (Frontiers in Plant Science, 2022)
FAR-RED ELONGATED HYPOCOTYLS3 (FHY3) and its homolog FAR-RED IMPAIRED RESPONSE1 (FAR1), which play pivotal roles in plant growth and development, are essential for the photo-induced phyA nuclear accumulation and subsequent photoreaction. The FAR1/FHY3 family has been systematically characterized in some plants, but not in Eucalyptus grandis. In this study, genome-wide identification of FAR1/FHY3 genes in E. grandis was performed using bioinformatic methods. The gene structures, chromosomal locations, the encoded protein characteristics, 3D models, phylogenetic relationships, and promoter cis-elements were analyzed with this gene family. A total of 33 FAR1/FHY3 genes were identified in E. grandis, which were divided into three groups based on their phylogenetic relationships. A total of 21 pairs of duplicated repeats were identified by homology analysis. Gene expression analysis showed that most FAR1/FHY3 genes were differentially expressed in a spatial-specific manner. Gene expression analysis also showed that FAR1/FHY3 genes responded to salt and temperature stresses. These results and observation will enhance our understanding of the evolution and function of the FAR1/FHY3 genes in E. grandis and facilitate further studies on the molecular mechanism of the FAR1/FHY3 gene family in growth and development regulations, especially in response to salt and temperature.